Education for Citizenship in Europe - European Policies, National Adaptations and Young People's Attitudes - Keating, Avril (Palgrave Macmillan UK, 2014)
This book examines the evolving relationship between the nation-state, citizenship and the education of citizens, exploring the impact European integration had on national policies towards educating its citizens and citizenship....